FORMULATION AND IN VITRO STUDY OF PROPRANOLOL HYDROCHLORIDE CONTROLLED RELEASE FROM CARBOXYMETHYL CHITOSAN-BASED MATRIX TABLETS - Hernawan Hernawan; Septi Nurhayati; Khoirun Nisa; A.W. Indrianingsih; Cici Darsih; Muhammad Kismurtono (Universitas Gadjah Mada, 2013)
Formulation and in vitro study of propranolol hydrochloride controlled release from carboxymethyl chitosan-based matrix tablets have been conducted. Formulations with various concentrations of carboxymethyl chitosan 2% (F1), 4% (F2), 6% (F3) were done by wet granulation method. Compatibility test was conducted by XRD and FTIR spectroscopy to determine interaction between propranolol hydrochloride and polymer excipients. Dissolution profiles was obtained through in vitro tests release using simulated gastric fluid (without enzymes, pH 1.2) for the first 2 h and followed by simulated intestinal fluid (phosphate buffer solution without enzyme, pH 7.2) for 2 h remaining. The dissolution profile of each formulation was fitted with five kinetics modeling of drug release (zero order, first order, Higuchi, Peppas-Korsmeyer, and Hixson-Crowell). The compatibility test results showed that formulation caused physical interactions between propranolol hydrochloride and polymer excipient but doesn't make crystallinity nature of propranolol hydrochloride disturbed even after formulation. Dissolution profiles of each formulation showed that controlled release of propranolol hydrochloride from the tablet followed Peppas-Korsmeyer model. It is concluded that carboxymethyl chitosan in appropriate proportions is suitable for formulating propranolol hydrochloride controlled release tablets which exhibit Peppas-Korsmeyer release kinetics.